Residents satisfaction or dissatisfaction with public sector governance: The Cretan case - Andriotis, Konstantinos (My University, 2002)
Local and national governments have at one point or another essential, or even critical influence over the local tourism industry for the provision of numerous services including infrastructure, transportation, security, overseas marketing, as well as funding of tourism projects. Observing a negligence of past research on the opinions of local community to public sector governance, the aim of this study was to investigate Cretan residents’ satisfaction or dissatisfaction with the role of local authorities and the Greek government in tourism development. Based on the findings, this paper discusses the implications of the research for future tourism policy and suggests future research priorities.
Keywords: Crete; Public sector governance; Residents’ opinions; Satisfaction; Tourism